Time patterns of recurrences and factors predisposing for a higher risk of recurrence of ocular toxoplasmosis - Reich, Michael; Ruppenstein, Mira Katharina; Becker, Matthias D.; Mackensen, Friederike (Retina, 2015)
Purpose: - To ascertain time patterns of recurrences and factors predisposing for a higher risk of recurrence of ocular toxoplasmosis. - Methods: - Retrospective observational case series with follow-up examination. Database of 4,381 patients with uveitis was used. Data of 84 patients with ocular toxoplasmosis (sample group) could be included. - Results: - Two hundred and eighty active lesions in the first affected eye were detected. The mean number of recurrences per year was 0.29 (standard deviation, 0.24). Median recurrence-free survival time was 2.52 years (95% confidence interval, 2.03-3.02 years). Risk of recurrence was highest in the first year after the most recent episode (26%) implying a decrease with increasing recurrence-free interval. The risk of recurrence decreased with the duration of disease (P < 0.001). Treatment of the first active lesion influenced the risk of recurrence (P = 0.048). Furthermore, the risk of recurrence was influenced by patient age at the time of the first active lesion (P = 0.021) and the most recent episode (P = 0.002). - Conclusion: - A secondary antibiotic prophylaxis could be discussed 1) during the first year after an active lesion has occurred, especially in case of the first active lesion of ocular toxoplasmosis, and 2) in older patients, especially if primarily infected with Toxoplasma gondii at an older age.
Gesehen am 17.06.2020